(untitled) (REGE Revista de Gestão, 2013)
Considering that the store image is an important marketing tool, which makes possible to identify the attributes with larger influence on consumers' satisfaction, the objective of the present research was to identify the image that consumers possess of a shoe store. The focus is to present the image that consumers have a shoe store. The study begins with a brief discussion on the retail footwear, starting soon after, a review of store image and its components and measurement scales. Thus, an empiric research was accomplished, through a descriptive approach, with the application of structured questionnaires. The target population was defined as being the customers of a shoe store in the city of São Sebastião do Paraíso (MG), whose sample was constituted by 123 respondents. In the data analysis, the factorial analysis was applied to identify the store image dimensions. As a result, seven factors of store image were obtained, that were nominated like this: assortment, convenience, reputation, price, atmosphere, layout and service. With this research’s results, it is believed that professionals and theoretical of the retail sector can better understand the role of the store image construct.